MODEL PEMBELAJARAN BERBASIS TPACK DALAM MENINGKATKAN PEMAHAMAN PESERTA DIDIK PADA MAPEL PAI DAN BP DI SMAN 1 KINALI - Suharjo Suharjo; Alizar Alizar; Andi Peta Wahyu Cahyono (CV. ADIBA AISHA AMIRA, 2024)
This study is entitled TPACK-Based Learning Model in Improving Students' Understanding of Islamic Religious Education Subjects at SMAN 1 Kinali. This study aims to evaluate the effectiveness of the application of the TPACK (Technological Pedagogical Content Knowledge) model in Islamic Religious Education (PAI) learning at SMAN 1 Kinali. The TPACK model integrates technology, pedagogy, and content knowledge to improve students' understanding of teaching materials while honing digital literacy skills. This study uses the Classroom Action Research (CAR) method which is implemented in three cycles, with stages of planning, action, observation, and reflection. The subjects of the study were grade XI students who studied the material